Enhancing Machine-Translated Tourism Texts: Post-Editing Practices of Indonesian Students - Dewi Kesuma Nasution; Bambang Panca Syahputra, (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This study investigates practices among students majoring in the English Education Study program at Universitas Muhammadiyah Sumatera Utara Indonesia in post-editing machine-translated tourism texts. Utilizing a descriptive qualitative approach, we analyzed the post-editing practices of these students. The texts postedited were authentic Indonesian tourism texts sourced from lonely planet website. The findings revealed machine translation errors in three main areas: lexico-semantic errors, grammatical errors, and syntactic errors. Lexico-semantic errors often involved incorrect word choices and mistranslations of nuanced terms. Grammatical errors were prevalent in the misuse of tense, agreement, and article usage. Syntactic errors included improper sentence structure and word order, leading to awkward or unclear translations. As a result of these errors, it was observed that students did some corrections to polish the machine translated text, from the most dominant type of correction to the least dominant, including correcting lexical choices, correcting word form, correcting word order, omissions, additions and deleting. It is recommended that future studies involve more diverse participants with different text types so as to generate a more comprehensive finding.